Genetic parameters and breeding values for daily milk production of Holstein cows in terms of heat stress - Vučković, Goran, agronom (Array, 2020)
In order to estimate the variance components as well as the breeding value for daily milk production of Holstein cows in terms of heat stress defined as different THI threshold values (68, 70, and 72) 1,275,713 test-day records from 90,159 cows were used. Temperature-humidity index (THI) calculated from ambient temperature and relative humidity recorded in the barns on the milk recording day was used as the measure of heat stress. Daily milk production was analysed as a bivariate variable, in the normal conditions (under the set THIthreshold value), and in terms of heat stress (above the set THIthreshold value) using a model that accounted variances due to lactation stage, calving season, age at calving, breeding region, parity, permanent environment, interaction between hear and year, and individual animal. The estimated high genetic correlations between the daily milk production in normal and heat stress conditions, as well as high correlations among the EBVs in normal and heat stress conditions, point out that Holstein cows with high productivity in normal condition will sustain an alike level of production even in terms of heat stress. These results indicate that the Holstein cows are very well acclimatized to the environmental conditions at dairy farms in Croatia. However, these findings should be taken with caution, given that measurements of microclimate parameters were conducted only once at a milk recording day, so the reliability of such measurements could be questionable. In conclusion, in order to realize a completely unambiguous conclusion, further studies that include multiple daily measurements of microclimatic parameters in the farms facilities are necessary.